Autologous thyroid cartilage graft implantation in medialization laryngoplasty: a modified approach for treating unilateral vocal fold paralysis - Ming-Shao Tsai (Nature Portfolio, 2017)
Abstract Medialization laryngoplasty is the standard surgical treatment for unilateral vocal fold paralysis. This study presents a modified approach in which a thyroid cartilage graft is implanted in medialization laryngoplasty. 22 patients who underwent this approach were included in the study. The results revealed that glottal incompetence and vocal performance were markedly improved following surgery, and the follow-up period ranged from 6 to 74 months (mean, 21.4 months). Acoustic analysis revealed significant improvements in the maximum phonation time (from 3.51 to 7.89 seconds, p < 0.001), F0 (from 221.7 to 171.0 Hertz, p = 0.025), and jitter (from 7.68 to 3.19, p < 0.001). Perceptual assessment revealed a significant decrease in voice grading (from 2.59 to 1.41, p < 0.001), roughness (from 1.82 to 1.23, p = 0.004), and voice breathiness (from 2.55 to 1.23, p < 0.001). None of the patients exhibited severe wound infection, tissue rejection, or other complications attributed to the surgical procedure. In conclusion, autologous thyroid cartilage implantation in medialization laryngoplasty medializes the vocal cord, minimizes the glottal gap, and improves the voice of patients with vocal fold paralysis. This procedure is characterized by simplicity, safety, and acceptable results.